Association of Hormonal Fingerprints with DMFT, BMI and Hemoglobin in 4-12 Years Old Children of Raichur - Reddy, Dr. K. M. Parveen; K, Dr. Anila; Saketh, Dr. D. Sumanth; Nagasudheer, Dr. Macha; Latha, Dr. H Aparna; Kurre, Dr. Bhaskar (International Journal of Innovative Research in Medical Science, 2025)
Introduction: Dental caries is hereditary and excessive caries run in households and are passed from mother to baby and run along generations. The early and correct detection and analysis of dental caries is a crucial thing for the general control of the dental patient. Presently, the so-called hormonal fingerprint additionally known as 2D:4D ratio has received a lot of research attention. The aim of the study is to evaluate the influence of digit ratio on the incidence of dental caries. Material and Methods: One hundred patients between 4 and 12 years participated in the study. Hormonal fingerprints (2D:4D ratio) was measured with the help of a digital vernier calliper. Caries incidence was recorded using the DMFT, Calculation of Body Mass Index and estimation of Hb levels was also done. Results: Out of 100 children 53 were males and 47 were females, in which 57% of males and 39% of females were with 2D:4D less than 1, 2% males and 17% females were having 2D:4D ≥1. Male population showed higher prevalence in the low 2D:4D ratio. Children with low 2D:4D ratio have excessive caries index, Low BMI values and Low Hb levels. Conclusion: The present study confirms the impact of hormones on Digit Ratio, BMI which in turn influence the caries index and could be used as an early predictor dental caries and Anaemia in children.